Web Based Libyan Food Ordering System - Aljarbi, Ahmed Abdalrazag A. (2010)
Normally customers have to wait in long queues to order their food making this a time consuming process. Online Food ordering systems are becoming a standard for restaurants who offer takeout and delivery services. Web based food ordering system have been designed with cost effective yet efficient system to handle restaurants needs. Through the online ordering system, restaurants have reduced cost; improved services and increased customer responsiveness. This study presents the system prototype for a web based Libyan food ordering system (WBLFOS). The design of the system was carried out according the industry standards using Unified Modeling Language and the prototype was implemented using ASP.net and Microsoft SQL Server 2008.